Etiological Profile of Children with Global Developmental Delay: A Single Center Study - Sachdeva, Pallavi; Sitaraman, Sadasivan; Minocha, Priyanka; Jain, Rohit; Choudhary, Anita; Jetha, Kapil (Journal of Pediatric Neurology, 2019)
Global developmental delay (GDD) is a relatively common pediatric issue. It can have plethora of causes. Early intervention in these children by finding the cause of developmental delay is often challenging but can definitely improve ultimate developmental outcome. The study was undertaken to study the clinical profile of children with GDD to assess the etiology of delay in these children. The study was performed in the Department of Pediatrics, SMS Medical College, Jaipur, from June 2014 to May 2015. One hundred sixty-eight children with GDD attending the child development clinic with age ≤ 5 years and development quotient < 70% were enrolled. After detailed clinical history and thorough examination, specific investigations were obtained. Data analysis was done to determine the underlying etiology. Out of 168 children studied, etiology was detected in 155 (92.3%). Most common etiology was perinatal insult (63.1%) followed by genetic (8.93%), postnatal (7.14%), metabolic (5.95%), mixed (2.98%), cerebral dysgenesis (2.38%), and congenital infections (1.79%). Microcephaly was present in 100 children. Most common etiology was found to be perinatal insult, which is a preventable cause to much extent. Newer and sophisticated investigations such as metabolic profile, genetic studies should be incorporated in the planned investigations to increase the diagnostic yield.
Keywords: developmental delay; etiology; perinatal; microcephaly